Biocompatibility and bioactive potential of the NeoMTA Plus endodontic bioceramic-based sealer - Roberto Alameda Hoshino; Mateus Machado Delfino; Guilherme Ferreira da Silva; Juliane Maria Guerreiro-Tanomaru; Mário Tanomaru-Filho; Estela Sasso-Cerri; Paulo Sérgio Cerri (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the biocompatibility and bioactive potential of NeoMTA Plus mixed as a root canal sealer in comparison with MTA Fillapex.Materials and MethodsPolyethylene tubes filled with NeoMTA Plus (n = 20), MTA Fillapex (n = 20), or nothing (control group, CG; n = 20) were inserted into the connective tissue in the dorsal subcutaneous layer of rats. After 7, 15, 30 and 60 days, the specimens were processed for paraffin embedding. The capsule thickness, collagen content, and number of inflammatory cells (ICs) and interleukin-6 (IL-6) immunolabeled cells were measured. von Kossa-positive structures were evaluated and unstained sections were analyzed under polarized light. Two-way analysis of variance was performed, followed by the post hoc Tukey test (p ≤ 0.05).ResultsAt 7 days, the capsules around NeoMTA Plus and MTA Fillapex had more ICs and IL-6-immunostained cells than the CG. However, at 60 days, there was no significant difference in the IC number between NeoMTA Plus and the CG (p = 0.1137) or the MTA Fillapex group (p = 0.4062), although a greater number of IL-6-immunostained cells was observed in the MTA Fillapex group (p = 0.0353). From 7 to 60 days, the capsule thickness of the NeoMTA Plus and MTA Fillapex specimens significantly decreased, concomitantly with an increase in the collagen content. The capsules around root canal sealers showed positivity to the von Kossa stain and birefringent structures.ConclusionsThe NeoMTA Plus root canal sealer is biocompatible and exhibits bioactive potential.